Management of Hypertension among Patients with Coronary Heart Disease - Oladipupo Olafiranye; Ferdinand Zizi; Perry Brimah; Girardin Jean-louis; Amgad N. Makaryus; Samy McFarlane; Gbenga Ogedegbe (International Journal of Hypertension)
Evidence suggests that coronary heart disease (CHD) is the most common outcome of hypertension. Hypertension accelerates the development of atherosclerosis, and sustained elevation of blood pressure (BP) can destabilize vascular lesions and precipitate acute coronary events. Hypertension can cause myocardial ischemia in the absence of CHD. These cardiovascular risks attributed to hypertension can be reduced by optimal BP control. Although several antihypertensive agents exist, the choice of agent and the appropriate target BP for patients with CHD remain controversial. In this succinct paper, we examine the evidence and the mechanisms for the linkage between hypertension and CHD and we discuss the treatment options and the goals of therapy that are consistent with the report of the seventh Joint National Committee on the Prevention, Detection, Evaluation, and Treatment of High Blood Pressure (JNC 7) and American Heart Association scientific statement. We anticipate changes in the recommendations of the forthcoming JNC 8.